2012
DOI: 10.1242/dev.075366
|View full text |Cite
|
Sign up to set email alerts
|

ROCK1-directed basement membrane positioning coordinates epithelial tissue polarity

Abstract: SUMMARYThe basement membrane is crucial for epithelial tissue organization and function. However, the mechanisms by which basement membrane is restricted to the basal periphery of epithelial tissues and the basement membrane-mediated signals that regulate coordinated tissue organization are not well defined. Here, we report that Rho kinase (ROCK) controls coordinated tissue organization by restricting basement membrane to the epithelial basal periphery in developing mouse submandibular salivary glands, and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 84 publications
7
59
0
Order By: Relevance
“…Rock1 plays pivotal roles in epithelial cell polarity by regulating PAR-1b activity and restricting basement membrane position (25), supporting that ROCK1 contributes to the polarity, proliferation, and differentiation of ameloblasts (9). In agreement with this, we found that Sp6 regulates ameloblast morphology and polarity by restoring polarization, alignment, and height of ameloblasts in Ami/Ami Tg rats with an Sp6 transgene (5).…”
Section: Discussionsupporting
confidence: 81%
“…Rock1 plays pivotal roles in epithelial cell polarity by regulating PAR-1b activity and restricting basement membrane position (25), supporting that ROCK1 contributes to the polarity, proliferation, and differentiation of ameloblasts (9). In agreement with this, we found that Sp6 regulates ameloblast morphology and polarity by restoring polarization, alignment, and height of ameloblasts in Ami/Ami Tg rats with an Sp6 transgene (5).…”
Section: Discussionsupporting
confidence: 81%
“…3B and Movie 2). In fact, polarity of such peripheral cells in direct contact with the basement membrane has been described previously (Daley et al, 2012). The outer bud cells periodically left the basement membrane and moved towards the bud interior accompanied by loss of their elongated, columnar shape, particularly when undergoing cell division (Movie 3).…”
Section: Region-specific Differences In Velocity and Morphology Durinsupporting
confidence: 56%
“…We recently used this adenoviral transfection/tissue recombination method to identify a role for the polarity protein, PAR-1b, in the control of the placement of basement membrane by the epithelium in developing salivary glands. Kinase-dead PAR-1b adenovirus and wild-type PAR-1b adenovirus were both used in this study 13 to infect epithelial rudiments and recombined with E13 mesenchymes. The ability to use mutant viruses to interrogate functions of specific molecules greatly enhances the utility of this method.…”
Section: Discussionmentioning
confidence: 99%
“…To directly assess effects of inhibitors on the epithelium, epithelial rudiments must be cultured in the absence of mesenchyme in either Matrigel or laminin-111 gels 6,7 . Small inhibitory RNAs (siRNAs) are an effective method to down-regulate epithelial gene expression since siRNAs are preferentially taken up by the epithelial cells in the presence of most lipid carriers 13,14,17,18 . However, neither of these methods for interfering with protein levels or function allow overexpression of a wild-type or mutant gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation